Literary creation and collective imaginary: Discussion on the concept of utopia in Latin American reality - Merino Trejos, Leonardo (2018)
This article discuss the concept of utopia concerning literary forms, in order to propose one who recovers this concept as a spirit from collective “imaginario”, expressed through literature as a human creation and expression. We also intend to review this concept based up to its expression in Latin America, where utopia is over the idea of site, gender, and regulator organizing model instead of an attitude of thought and a constant spirit in collective “imaginario”. Some concepts of utopia are reviewed to separate this one from the text itself and to tie it to its own “imaginario”.